Microstructure and properties of rare earth CeO2-doped TiO2 nanostructured composite coatings through micro-arc oxidation. Issue 5 (June 2015) - Di, Shichun; Guo, Yupeng; Lv, Hongwei; Yu, Jie; Li, Zhenwei
Abstract: Rare earth cerium oxide (CeO2 ) – doped TiO2 nanostructured composite coatings were obtained through micro-arc oxidation technique on titanium substrates. The surface hardness and corrosion resistance of the substrates were improved. The results of X-ray diffraction, energy dispersive spectrum, and X-ray photoelectron spectroscopy show that the composite coatings mainly consist of rutile-TiO2, anatase-TiO2, and CeO2 . The CeO2 content was increased by increasing the current density and electrolyte concentration. CeO2 was observed on the surface as well as in the deep layers. The scanning electron microscopy results display that the number of micro-holes decreased. The holes became bigger, and a smooth area appeared around the micro-holes. The surface roughness of the composite coatings was initially reduced but subsequently increased with increasing CeO2 concentration, while the thickness of the composite coatings increased. The results demonstrated that the surface hardness of the coatings was enhanced to 609.17 Hv at the CeO2 concentration of 4 g/L, and the corrosion current decreased to 1.584e -007 A at 6 g/L.